# How do you find #f(g(-3))# given #f(x)=2x-1# and #g(x)=3x# and #h(x)=x^2+1#?

Evaluate f(g(-3)) by substituting -3 into g(x), then take that result and substitute it into f(x). The final expression is 15.

By signing up, you agree to our Terms of Service and Privacy Policy

See a solution process below:

By signing up, you agree to our Terms of Service and Privacy Policy

- The product of two consecutive integers is 482 more than the next integer. What is the largest of the three integers?
- How do you find 4x - 2y - z, if x = 2, y = 3, and z = -8?
- How do you evaluate #(5wx)/z# if w=6, x=0.4, y=1/2, z=-3?
- How do you write using variables: Ten is seven more than a number?
- How do you simplify #4+6/2+3#?

- 98% accuracy study help
- Covers math, physics, chemistry, biology, and more
- Step-by-step, in-depth guides
- Readily available 24/7